Primeiro Comando da Capital e seu fortalecimento nacional - Vicente, Ariane (Universidade Federal de São Carlos, 2024)
In 1993, the state of São Paulo went through the expansion of a criminal organization named Primeiro Comando da Capital (PCC), which was responsible for many of the rebelions experienced by the Brazilian prison system, always causing countless deaths and safety demands for the inmates. According to this, the goal of this study is to discuss the urban violence seen in the 80’s decade, still prevailing nowadays, and how criminal organizations are linked to this problem. The methodology used is based on bibliographical review, so that the search of studies on this theme is efficient and relevant. It is noticeable, with the obtained data, that prison system’s criminality and the emergence of gangs like PCC and Comando Vermelho (CV) prove to be strong, with defined leadership, numerous members, statutes and well distributed activities. It soon comes clear that urban violence goes through these organizations, which usually control drug smuggling routes and make use of death as means of fearing and respecting their leaders.
Primeiro Comando da Capital and its national empowerment
Keywords: Violência Urbana; Criminalidade; PCC; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS